Upacara Pernikahan dan Tata Rias Pengantin di Kecamatan Pauh Kota Padang Sumatera Barat - Rahmadhani, Suci; Rahmiati, Rahmiati; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The background of this research is the fact that the wedding ceremony and bridegroom makeup in Minangkabau is known in general in the society and the further details of this procession are only known by some particular local people in the custom. The researcher discovers that there is the difference in wedding ceremony in Kecamatan Pauh and other kecamatan in Padang, West Sumatera. The goal of this research is to discover more about the wedding ceremony and the bridegroom makeup in Kecamatan Pauh, Padang, West Sumatera. This research use qualitative research method in order to dig in a more detail information regarding the wedding ceremony and bridegroom makeup in Kecamatan Pauh, Padang, West Sumatera. The object of this research is the wedding ceremony and bridegroom makeup, and the informants in this research are four people who know the detail information about the wedding ceremony and bridegroom makeup in Kecamatan Pauh, Padang. The data is collected by doing observation, interview, documentation and the data analysis is data triangulation and reduction.The result of this research shows that the wedding ceremony and its’ sequence have some differences in the tradition between Kecamatan Pauh and other areas in Padang. In Kecamatan Pauh, the old tradition is the guide for the present tradition, even though there are some parts that have changed. The clothes of the bridegroom in the old days is pretty different with the present clothes. Thus, a clearer information about the wedding ceremony and bridegroom makeup in Kecamatan Pauh, Padang is obtained to be known for the next generation and can be conserved in the future so that this tradition will not disappear later.Kata kunci : Wedding ceremony, cosmetologys